The Association Between Breast Cancer and Blood-Based Methylation of S100P and HYAL2 in the Chinese Population - Yin, Qiming; Yang, Xiaoqin; Li, Lixi; Xu, Tian; Zhou, Wenjie; Gu, Wanjian; Ma, Fei; Yang, Rongxi (Frontiers in Genetics, 2020)
Previous work has shown that DNA methylation in peripheral blood may be associated with malignancy; however, these studies have mainly been conducted within Caucasian populations. Here, we investigated the association between blood-based methylation of S100 calcium-binding protein P gene (S100P) and hyaluronoglucosaminidase 2 gene (HYAL2) and breast cancer (BC) via mass spectrometry in two independent case-control studies of the Chinese population with a total of 351 BC cases and 427 cancer-free female controls. In Study I, in which subjects had an average of 45 years, hypomethylation of S100P showed a protective effect for women ≤45 years (six out of nine CpG sites, p < 0.05) but not for women >45 years. In contrast, hypomethylation of HAYL2 was not correlated with BC in women ≤45 years but was a risk factor for women >45 years (three out of four CpG sites, p < 0.05). We proposed an age-dependent correlation between BC and methylation of S100P and HYAL2 and performed further validation in Study II with older subjects (average age = 52.5 years), where hypomethylation of both S100P and HYAL2 was a risk factor for BC (p < 0.05 for 10 CpG sites) as reported in Caucasians who develop BC around 55 years old. Together with the observation that Chinese cancer-free females having variant basal methylation levels comparing to Caucasians, we assumed that blood-based methylation might be modified by ethnic background, hormone status, and lifestyle. Here, we highlighted that the epigenetic biomarkers warrant validations when its application in variant ethnic groups is considered.